Desain Interaksi Website Edukasi Kekerasan Seksual di Era Digital Menggunakan Metode Design Sprint: Studi Kasus PPKS Institut Teknologi Telkom Purwokerto - Alissyah Putri; Rifki Adhitama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Telkom Purwokerto Institute of Technology is one of the Private Higher Education Institutions in Indonesia. The Telkom Purwokerto Institute of Technology has three faculties and fifteen study programs. To support all campus activities, this university has various types of facilities. One of the campus facilities is the availability of sexual violence handling services on campus. In the implementation of this service, there are still problems that occur, so a task force team named PPKS (Prevention and Handling of Sexual Violence) was formed. Over time, the current service system wants to be further developed into a better system in the future. During the research, problems were found, especially in terms of information delivery media. Based on these problems, the researcher wants to perform interaction design for the PPKS ITTP task force team website using the Design Sprint method. There are 5 stages that will be implemented. Namely Mapping, Sketching, Decide, Prototype, and Validate. This research will produce a final prototype (prototype of the result) that can be used for the development of the PPKS ITTP website. The results of the final prototype are Home-B (91.7%), Profile-B (90.8%), Module-B (91.7%), Quiz-B (92.7%) and Complaint-B (91.7%).